The Lego Batman movie - Grahame-Smith, Seth; Lin, Dan, (Film producer); McKay, Chris; Arnett, Will; Galifianakis, Zach; Cera, Michael; Dawson, Rosario; Fiennes, Ralph; Burrows, David; Villa, Matt; Warner Bros. Pictures (1969- ); Lin Pictures (Firm); et al. (Burbank, CA : Warner Bros. Home Entertainment, 2017)
In the irreverent spirit of fun that made The LEGO Movie a worldwide phenomenon, the self-described leading man of that ensemble, LEGO Batman, stars in his own big-screen adventure. But there are big changes brewing in Gotham, and if he wants to save the city from the Joker's hostile takeover, Batman may have to drop the lone vigilante thing, try to work with others, and maybe, just maybe, learn to lighten up.
Title from disc label.
DVD release of the 2017 motion picture.
Special features: 4 new original animated shorts ; 4 deleted scenes ; 6 featurettes.
Editor, David Burrows, Matt Villa, John Venzon ; music, Lorne Blafe.
Voices, Will Arnett, Zach Galifianakis, Michael Cera, Rosario Dawson, Ralph Fiennes.
MPAA rating: PG; for rude humor and some action.
Keywords: Batman -- (Fictitious character) -- Drama; Joker -- (Fictitious character) -- Drama; LEGO toys -- Drama; Superheroes -- Drama; Children's films; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Animated films